Forest Ordinance (Sarawak), Cap.126: its effectiveness and weakness / Logie Seman - Seman, Logie (1987)
This study highlights on the effectiveness and weakness of the Forests Ordinance (Sarawak) Cap.126 on its application and limitations, the apprehension of forest offenders, social-economic aspects and some matters related to timber licences. Focus is given to precedented court cases and to what extent the provisions concerned be effective so far litigated. It also touches on the administrative disposal of forest offences by virtue of quasi-judicial power conferred under Section 70 of the ordinance. Briefly, it also shows how the ordinance affects the socioeconomic aspects especially the natives of Sarawak. Lastly, it examines some economic values and impacts of timber licences on environment and rural dwellers. Some recommendations are put forward in this study.